Politeness Strategy in Commissive Speech Acts - Devi Mulatsih Mudiharjo; Tajudin Nur; Lia Maulia Indrayani; Nani Darmayanti (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Understanding comissive speech acts is important in oral or written communication because humans are often facing problems in communicating using language. So, someone can take action under the meaning, intention, and purpose of their utterance.  In every speech act, not only the context, but also the utterance cannot be separated from the use of verbal utterance. This study specifically aims to describe and explain about politeness in commissive speech acts in a variety of speech situations. The research method used is the descriptive analysis method. The data in this study are the form of utterances contain in the conversation of film. The results of this study are founds 4 (four) types of commissive speech acts, they are: promise, swear, pledge (berniat), and vow (bernadar). While the politeness strategies in commissive speech acts include: (i) Cost-Benefit Scale found in promise, (ii) Optionally Scale in swear and pledge, (iii) Indirectness Scale found in promise, swear, and vow, (iv) Authority Scale found in swear that, (v) Social Distance Scale found in pledge.